Individually dosed omalizumab facilitates peanut oral immunotherapy in peanut allergic adolescents - Brandström, Josef; Vetander, Mirja; Sundqvist, Ann‐Charlotte; Lilja, Gunnar; Johansson, S. G. O.; Melén, Erik; Sverremark‐Ekström, Eva; Nopp, Anna; Nilsson, Caroline (Clinical and experimental allergy, 2019)
Background Peanut oral immunotherapy (pOIT) has showed good short‐term outcomes, but allergic reactions may prevent effective up‐dosing and is a major cause of stopping OIT. In placebo‐controlled trials, omalizumab has been shown to facilitate allergen immunotherapy and increase tolerance to peanut. Objective We hypothesized that by combining omalizumab with pOIT, and monitor treatment effects with basophil allergen threshold sensitivity tests (CD‐sens), peanut allergic patients could safely initiate pOIT and thereafter slowly withdraw omalizumab. Methods This is the 2nd part of a one‐armed open phase‐2 study where peanut allergic adolescents (n = 23) started pOIT after an individualized omalizumab treatment. The pOIT dose was increased from 280 to 2800 mg peanut protein in 8 weeks followed by an individualized step‐wise withdrawal of omalizumab, based on clinical symptoms and CD‐sens levels. pOIT continued for 12 weeks followed by an open peanut challenge. Peanut CD‐sens and allergen‐binding activity (ABA) and IgE‐ab, IgG‐ab and IgG4‐ab to peanut and its components were measured during the study. Results All 23 patients successfully reached the 2800 mg maintenance dose. Moderate/systemic allergic reactions were rare while receiving full‐dose omalizumab. Eleven of 23 (48%) successfully continued with pOIT after omalizumab was stopped. Compared to treatment failures, median baseline IgE‐ab to peanut components Ara h 1‐3 and CD‐sens to peanut were significantly lower among successfully treated patients and IgG4‐ab to peanut, Ara h 2 and 6 increased significantly more during treatment. Conclusions and clinical relevance This study indicates that omalizumab is an effective adjunctive therapy for initiation and rapid up‐dosing of pOIT; however, adverse events from pOIT become more frequent as omalizumab doses are decreased. Clinical trials registration: ClinicalTrials.gov; NCT02402231. EudraCT; 2012‐005625‐78.